Pengaruh Terapi Relaksasi Otot Progresif Terhadap Penurunan Tekanan Darah Pada Lansia Di UPTD Puskesmas Tanjung Unggat - Reza Novizar Syah; Mira Agusthia; Rachmawaty M. Noer (Lembaga Pengembangan Kinerja Dosen, 2024)
The prevalence of hypertension in Indonesia reaches 34.11%, with the highest incidence of hypertension found in those aged 65 years and over at 63.22%. The number of elderly patients suffering from hypertension who undertake non-pharmacological therapy needs to be encouraged. Non-pharmacological therapy is always an option because it is not expensive, one of which is progressive muscle relaxation. Research objective: to determine the effect of progressive muscle relaxation therapy on reducing blood pressure in the elderly at the Tanjung Unggat Community Health Center UPTD. Quasi Experiment with One Group Pre-Post Test Design approach. The sample consisted of 26 elderly respondents who suffered from hypertension in the UPTD area of ​​the Tanjung Unggat Community Health Center using a purposive sampling technique. The mean systolic and diastolic blood pressure before progressive muscle relaxation therapy was 152.50 mmHg and 94.81 mmHg. After treatment with progressive muscle relaxation therapy, the mean systole was 138.85 mmHg and the mean diastole was 88.62 mmHg. The results of the Wilcoxon Sign Rank Test statistical test obtained p-value = 0.000 (p < 0.05), namely H0 was rejected, which means there was an effect of providing progressive muscle relaxation therapy on reducing blood pressure in the elderly at the UPTD Tanjung Unggat Health Center. It is hoped that the elderly can apply progressive muscle relaxation to lower blood pressure.